Mesenchymal Stem Cell Derived Biocompatible Membrane Vesicles Demonstrate Immunomodulatory Activity Inhibiting Activation and Proliferation of Human Mononuclear Cells - Marina O. Gomzikova; Sevindzh K. Kletukhina; Sirina V. Kurbangaleeva; Olga A. Neustroeva; Olga S. Vasileva; Ekaterina E. Garanina; Svetlana F. Khaiboullina; Albert A. Rizvanov (MDPI AG, 2020)
Immune-mediated diseases are characterized by abnormal activity of the immune system. The cytochalasin B-induced membrane vesicles (CIMVs) are innovative therapeutic instruments. However, the immunomodulating activity of human mesenchymal stem cell (MSC)-derived CIMVs (CIMVs-MSCs) remains unknown. Therefore, we sought to investigate the immunological properties of CIMVs-MSCs and evaluate their effect on human peripheral blood mononuclear cells (PBMCs). We found that CIMVs-MSCs are primarily uptaken by monocytes and B-cells. Additionally, we demonstrated that CIMVs-MSCs inhibit phytohemagglutinin (PHA)-induced proliferation of PBMCs, with more pronounced effect on T-lymphocytes expansion as compared to that of B-cells. In addition, activation of T-helpers (CD4+CD25+), B-cells (CD19+CD25+), and T-cytotoxic lymphocytes (CD8+CD25+) was also significantly suppressed by CIMVs-MSCs. Additionally, CIMVs-MSCs decreased secretion of epidermal growth factor (EGF) and pro-inflammatory Fractalkine in a population of PBMCs, while the releases of FGF-2, G-CSF, anti-inflammatory GM-CSF, MCP-3, anti-inflammatory MDC, anti-inflammatory IL-12p70, pro-inflammatory IL-1b, and MCP-1 were increased. We analyzed the effect of CIMVs-MSCs on an isolated population of CD4+ and CD8+ T-lymphocytes and demonstrated their different immune response and cytokine secretion. Finally, we observed that no xenogeneic nor allogeneic transplantation of CIMVs induced an immune response in mice. Our data suggest that CIMVs-MSCs have immunosuppressive properties, are potential agents for immunomodulating treatment, and are worthy of further investigation.